2022
DOI: 10.5109/6622879
|View full text |Cite
|
Sign up to set email alerts
|

Energy Conservation of Smart Grid System Using Voltage Reduction Technique and Its Challenges

Abstract: Energy conservation has become crucial due to the present energy crisis in the world. To resolve such crises and reduce peak hours' electricity demand, the conservation voltage reduction (CVR) technique is frequently implemented in the power grid system. In this paper, experimental work along with simulation has been done to conserve energy by employing the CVR technique in a smart grid (SG). To verify the simulation result, an Arduino-based SG has been designed with a realtime clock (RTC) and Wi-Fi module esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 59 publications
0
31
0
1
Order By: Relevance
“…In fact, the study showed that high turmeric levels (>5%) could lead to complete developmental arrest (Hellfeld et al, 2023). The molecular mechanisms through which turmeric -or compounds therein -leads to toxicity in insects is uncertain but Rahman et al, (2022) found that higher concentrations of turmeric (>1%) in the diet decreased β-tubulin levels in the brain and affected a range of physiological traits of D. melanogaster. The study also found that an optimal dosage of 0.5% of turmeric could maintain healthy aging by increasing β-tubulin expression.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the study showed that high turmeric levels (>5%) could lead to complete developmental arrest (Hellfeld et al, 2023). The molecular mechanisms through which turmeric -or compounds therein -leads to toxicity in insects is uncertain but Rahman et al, (2022) found that higher concentrations of turmeric (>1%) in the diet decreased β-tubulin levels in the brain and affected a range of physiological traits of D. melanogaster. The study also found that an optimal dosage of 0.5% of turmeric could maintain healthy aging by increasing β-tubulin expression.…”
Section: Discussionmentioning
confidence: 99%
“…known as it is used as an effective anti-epileptic agent and has applications in treating bipolar disorder and migraine. [147] All these complexes were studied as antimalarial agents by testing their β-hematin formation inhibition ability using a semiquantitative method. [148] 1 mg/ml concentration of the complexes was used, and the inhibition ability was monitored by measuring the absorbance at 405 nm (β-hematin characteristic band).…”
Section: Antimalarial Activity Of 3 D Metal-based Complexesmentioning
confidence: 99%
“…The study shows that a number of institutions have been formed and important initiatives have been taken to meet the targets set for achieving SDGs, among which SREDA formation and home electrification are most important. Bangladesh is also moving towards sustainable renewable energy capacity by launching important installations such as mini-grids, wind power plants, and biogas plants [57].…”
Section: Steps Taken By Bangladesh In the Renewable Energy Sector To ...mentioning
confidence: 99%